Nanofibrous Vildagliptin/PLGA Membranes Accelerate Diabetic Wound Healing by Angiogenesis - Chen-Hung Lee; Chien-Hao Huang; Kuo-Chun Hung; Shu-Chun Huang; Chi-Ching Kuo; Shih-Jung Liu (MDPI AG, 2022)
The inhibition of dipeptidyl peptidase-4 (DPP4) significantly enhances the wound closure rate in diabetic patients with chronic foot ulcers. DPP4 inhibitors are only prescribed for enteral, but topical administration, if feasible, to a wound would have more encouraging outcomes. Nanofibrous drug-eluting poly-D-L-lactide-glycolide (PLGA) membranes that sustainably release a high concentration of vildagliptin were prepared to accelerate wound healing in diabetes. Solutions of vildagliptin and PLGA in hexafluoroisopropanol were electrospun into nanofibrous biodegradable membranes. The concentration of the drug released in vitro from the vildagliptin-eluting PLGA membranes was evaluated, and it was found that effective bioactivity of vildagliptin can be discharged from the nanofibrous vildagliptin-eluting membranes for 30 days. Additionally, the electrospun nanofibrous PLGA membranes modified by blending with vildagliptin had smaller fiber diameters (336.0 ± 69.1 nm vs. 743.6 ± 334.3 nm, p < 0.001) and pore areas (3405 ± 1437 nm2 vs. 8826 ± 4906 nm2, p < 0.001), as well as a higher hydrophilicity value (95.2 ± 2.2° vs. 113.9 ± 4.9°, p = 0.004), and showed a better water-retention ability within 24 h compared with PLGA membranes. The vildagliptin-eluting PLGA membrane also enhanced the diabetic wound closure rate for two weeks (11.4 ± 3.0 vs. 18.7 ± 2.6 %, p < 0.001) and the level of the angiogenesis using CD31 expression (1.73 ± 0.39 vs. 0.45 ± 0.17 p = 0.006 for Western blot; 2.2 ± 0.5 vs. 0.7 ± 0.1, p < 0.001 for immunofluorescence). These results demonstrate that nanofibrous drug-eluting PLGA membranes loaded with vildagliptin are an effective agent for sustained drug release and, therefore, for accelerating cutaneous wound healing in the management of diabetic wounds.